2019
DOI: 10.1001/jamadermatol.2018.5459
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of Clinical Grading Measures for Cutaneous Chronic Graft-vs-Host Disease

Abstract: IMPORTANCE Cutaneous chronic graft-vs-host disease (cGVHD) is common after allogeneic hematopoietic stem cell transplant and is often associated with poor patient outcomes. A reliable and practical method for assessing disease severity and response to therapy among these patients is urgently needed. OBJECTIVE To evaluate the interrater agreement and reliability of skin-specific and range of motion (ROM) variables of the 2014 National Institutes of Health (NIH) response criteria for cGVHD and a skin sclerosis g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Most importantly, specific details on the various types of skin involvement were not provided. Because most patients had skin sclerosis, the very poor agreement in scoring of the subtypes of epidermal skin involvement, seen in Table 2 of the study, may reflect the small sample size of certain epidermal features or overlapping clinical features in some patients. Furthermore, the clinical subtype of skin disease greatly influences the ability to accurately score skin GVHD by BSA.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Most importantly, specific details on the various types of skin involvement were not provided. Because most patients had skin sclerosis, the very poor agreement in scoring of the subtypes of epidermal skin involvement, seen in Table 2 of the study, may reflect the small sample size of certain epidermal features or overlapping clinical features in some patients. Furthermore, the clinical subtype of skin disease greatly influences the ability to accurately score skin GVHD by BSA.…”
mentioning
confidence: 92%
“…In the study by Cardones and colleagues published in this issue of JAMA Dermatology , the authors take a step toward improving GVHD skin assessment by testing the interrater reliability of skin grading between transplant physicians and dermatologists at their institution. A panel of 6 blood and marrow transplant (BMT) specialists and 4 medical dermatologists evaluated a cohort of 8 patients (6 with skin sclerosis) according to the current NIH Consensus Response Criteria Working Group recommendations for grading of skin GVHD, as well as range of motion assessment for joint and fascial GVHD .…”
mentioning
confidence: 99%
“…The current reference-standard response measure used for therapy approval in clinical trials is the NIH Skin Score, which correlates with clinician-reported perception of change and survival outcomes . However, studies also demonstrate that the NIH Skin Score can be subject to poor inter-rater reliability and responsiveness to change . PROs are increasingly found to be discordant, and thus provide complementary information to clinical assessment measures .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcome measures for cutaneous fibrosing disorders have limitations in the detection of early disease, prediction of outcome, or evaluation of response to therapy (Aki et al, 2016;Baird et al, 2013;Kelsey and Torok, 2013). Inter-rater agreement can be poor, even among specialists (Cardones et al, 2019;Clements et al, 1995). Therefore, a great need .…”
mentioning
confidence: 99%